Narrow-gap semiconductors and low-dimensional structures for optoelectronic applications - Yue, Fangyu; Jit, Satyabrata; Hu, Weida (ScientificWorld Ltd., 2014)
[No abstract available]
Keywords: Narrow-gap semiconductors; low-dimensional structures; optoelectronic applications